Do women with complex alcohol and other drug use histories want women‐only residential treatment?. (24th January 2018) - Neale, Joanne; Tompkins, Charlotte N. E.; Marshall, Alison D.; Treloar, Carla; Strang, John
Abstract: Background: Women‐only addiction services tend to be provided on a poorly evidenced assumption that women want single‐sex treatment. We draw upon women's expectations and experiences of women‐only residential rehabilitation to stimulate debate on this issue. Methods: Semi‐structured interviews were undertaken with 19 women aged 25–44 years [currently in treatment ( n  = 9), successfully completed treatment ( n  = 5), left treatment prematurely ( n  = 5)]. All had histories of physical or sexual abuse, and relapses linked to relationships with men. Interviews were audio‐recorded, transcribed verbatim, coded and analysed inductively following Iterative Categorization. Findings: Women reported routinely that they had been concerned, anxious or scared about entering women‐only treatment. They attributed these feelings to previous poor relationships with women, being more accustomed to male company and negative experiences of other women‐only residential settings. Few women said that they had wanted women‐only treatment, although many became more positive after entering the women‐only service. Once in treatment, women often explained that they felt safe, supported, relaxed, understood and able to open up and develop relationships with other female residents. However, they also described tensions, conflicts, mistrust and social distancing that undermined their treatment experiences. Conclusions: Women who have complex histories of alcohol and other drug use do not necessarily want or perceive benefit in women‐only residential treatment.